Photo displays and intergenerational relationships in the family home - Durrant, Abigail; Taylor, Alex; Frohlich, David; Sellen, Abigail; Uzzell, David (Proceedings of British HCI 2009, 2009)
In this paper we describe a design-orientated field study in which we deploy a novel digital display device to explore the potential integration of teenage and family photo displays at home, as well as the value of situated photo display technologies for intergenerational expression. This exploration is deemed timely given the contemporary take-up of digital capture devices by teenagers and the unprecedented volume of photographic content that teens generate. Findings support integration and the display of photos on a standalone device, as well as demonstrating the interventional efficacy of the design as a resource for provoking reflection on the research subject. We also draw upon the theoretical concept of Dialogism to understand how our design mediates intergenerational relationships and interaction aesthetics relating to the notion of 'constructive conflict'.
Winner Archival Highlight Prize